What Is The Role Customer Relationship Management Towards Customer Satisfaction - Pesik, Iren Meiske (Journal of Management, 2023)
Finding and examining the framework for customer relationship management that UKM Aminda Cake used throughout the epidemic is the goal of this study. MSMEs face a number of issues, including declining revenue, declining demand, shipping and logistics, scarce resources, and future uncertainty. In this study, surveys and observation were the methods employed. The findings of the study demonstrate that customer identification, interaction management, service personalisation, complaint management, customer data analysis, and SWOT analysis comprise the CRM framework that has been implemented in SMEs. The CRM architecture has a number of drawbacks, including high implementation costs, insufficient internal resources, and low employee adoption and involvement